Кургани центральної частини Сянсько-Дністрянської височини - Махнік, Я.; Павлів, Д.; Петегирич, В. (Інститут українознавства ім. І. Крип'якевича НАН України, 2009)
Territory between Wyshnya and Stryvihor Rivers on San-Dnister Upland till recently was a “white spot” on the map of burial mound sites of region of upper Dnister River. 429 mounds were discovered here. Part of them is situated separately, but more are composed in groups. Near the villages of Balychi, Bykiw and Pnikut the giant single barrows are situated. The most of them, nearby Komarovychi, have about 40 m in diameter, and height over 9 m. Especially large concentration of barrows (177 mounds) is discovered on a small territory between the villages of Yordanivka-Bolyanovychi-Chyzhky-Rogizno-Verkhivci. Most of these barrows are dated, probably, to the end of Eneolithic Age, early and middle periods of the Bronze Age. Near-by the villages of Hatky and Bykiw hill-fort and two barrow cemeteries from Early Mediaeval Period were found. The area between Wyshnya and Stryvihor Rivers is one of the most saturated by burial mounds in a Sub-Carpathian region.